Ganoderma lucidum polysaccharides encapsulated in liposome as an adjuvant to promote Th1-bias immune response. (20th May 2016) - Liu, Zhenguang; Xing, Jie; Zheng, Sisi; Bo, Ruonan; Luo, Li; Huang, Yee; Niu, Yale; Li, Zhihua; Wang, Deyun; Hu, Yuanliang; Liu, Jiaguo; Wu, Yi
Abstract : Highlights: GLPL/OVA were able to maintain good colloidal stability and higher OVA-EE when stored at 4 °C. GLPL/OVA could induce more powerful antigen-specific immune responses. GLPL/OVA generate a stronger Th1-biased immune response. The strong immune response of GLPL/OVA might be attributed to efficient activation and mature of DC in draining lymph nodes. Abstract: Liposome-based vaccine delivery systems are known to enhance immune responses. Ganoderma lucidum polysaccharides (GLP) have been widely studied as immunomodulator and it could be as inducers of strong immune responses. In the research, GLP and ovalbumin (OVA) were encapsulated into liposome as vaccine and inoculated to mice. The magnitude and kinetics of the humoral and cellular immune responses were investigated. The results showed that GLP–OVA-loaded liposomes (GLPL/OVA) could induce more powerful antigen-specific immune responses than each single-component formulation. Mice immunized with GLPL/OVA displayed higher antigen-specific IgG antibodies, better splenocytes proliferation, higher cytokine secretion by splenocytes and significant activation of CD3 + CD4+ and CD3 + CD8+ T cells. Thus the GLPL/OVA formulation produced a heightened humoral and cellular immune response, with an overall Th1 bias. Enhanced immune responses elicited by the GLPL/OVA formulation might be attributed to effective activation and mature of DC in draining lymph nodes. Overall, these findings indicate that GLPL have the potential to enhance immune responses as vaccine delivery systems.